Translation and repetition: Rewriting (un)original literature - Leiva Rojo, Jorge (TRANS: Revista de Traductología, 2023)
Reseña de Translation and repetition: Rewriting (un)original literature Vidal Claramonte, M.ª Carmen África Routledge, Londres y Nueva York, 2023, 161 pp.